Ethnic variation in the susceptibility to diabetes - Shaw, Jonathan (Henry Stewart Talks, 2020)
Different type of diabetes exhibits diverse ethnic patterns of diabetes, T1D diabetes in people of European origin, T2D diabetes in Non-European and indigenous populations, High rates of T1D and T2D among some middle eastern countries, T2D in South Asian populations caused by increased visceral fat and poorer beta cell function, Association of early onset T2D with high risk of the disease, Ethnicity and complication rates, Personal cost burden of complications in lower and middle income countries